Prognostic model of socio-pedagogical assistance to employment of university graduates - Ljubov G. Pak; Elena G. Kameneva; Ljubov A. Kochemasova; Yulia A. Sokolova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The paper presents theoretical and methodological grounds that update the development of a prognostic model of social and pedagogical assistance to the employment of university graduates. Problems and risks have been identified that objectively impede the entry of young people into the labor market and the negative consequences (effects) of the employment of young specialists for themselves, educational organizations of higher education, and in general, the state. On the basis of interdisciplinary analysis of domestic and foreign scientific literature, advanced pedagogical experience, the basic concepts of research were clarified and the block structure of the prognostic model of social and pedagogical assistance to the employment of university graduates was substantiated. The paper describes the interrelated target, methodological, meaningful, organizational and technological, productive blocks of the authors model. A target block of the model is presented, reflecting the target guidelines for providing social and pedagogical assistance to the employment of university graduates on the basis of analyzing the social order of society for productive primary employment of university students, studying regulatory documents in the fields of education, labor, economics, and employment centers. The methodological block of the authors model was characterized, reflecting the conceptual ideas of acmeological and activity scientific approaches, patterns and the general scientific principles arising from them (professional orientation; focus on self-development of key competencies; subjectivity; expediency and conscious perspective; activity polyphonism). A meaningful block of the prognostic model is presented, aimed at the phased implementation of semantic guidelines (subjectivity, facilitation, partnership), strategies (updating the professional and personal potential of young specialists; socio-pedagogical orientation of students to successful self-presentation; activating professional self-determination and granting the right to choose; scaffolding), methods and forms of prognostic orientation of the studied phenomenon. The organizational and technological unit of the authors model describing the set of organizational conditions of the optimal functioning of the model is considered. An effective block of the prognostic model of social and pedagogical assistance to the employment of university graduates is presented, which performs feedback functions and allows, during the justification of the criterion and diagnostic tools, to determine the dynamics and level of formation of the culture of employment of university graduates (as a result of the authors model).